Дослідження на Цитаделі Гетьманської столиці у 2008 р. - Коваленко, В.П.; Ситий, Ю.М.; Терещенко, О.В. (Археологічні дослідження в Україні, 2009)
The results of the research of archaeological monuments within the protected areas of Baturyn State Historic and Cultural Preserve «Hetman’s Capital» in 2008 are published in the paper.